ІДЕНТИФІКАЦІЯ МАТЕМАТИЧНОЇ МОДЕЛІ ТУРБОАГРЕГАТА З НАЯВНІСТЮ НЕВИЗНАЧЕНОСТІ - Балюта, С.М.; Черненко, П.О.; Куєвда, Ю.В.; Куєвда, В.П. (Інститут електродинаміки НАН України, Київ, 2021)
An identification procedure of mathematical model of turbine generator unit in the presence of uncertainty is studied for using in the interconnected robust control automated system. The procedure is based on “worst-case” identification approach. The controlled object is modelled by the matrix transfer function with additive uncertainty. The identification consists of two stages: first is to identify transfer function with nominal parameters with the use of prediction error minimization algorithm, second – to determine weight function in additive uncertainty model using finding the worst-case log-magnitude curve of uncertainties. Identification is performed in active way, determining datasets for each control channel from individual experiments. A linear frequency-modulated signal is selected as the input test disturbance. A simulation model of the controlled object is constructed and the numerical experiment is conducted using the identification procedure. References 11, figures 7.